iRECIST: how to do it - Persigehl, Thorsten (Cancer Imaging, 2020)
BACKGROUND: iRECIST for the objective monitoring of immunotherapies was published by the official RECIST working group in 2017. MAIN BODY: Immune-checkpoint inhibitors represent one of the most important therapy advancements in modern oncology. They are currently used for treatment of multiple malignant diseases especially at advanced, metastatic stages which were poorly therapeutically accessible in the past. Promising results of recent studies suggest that their application will further grow in the near future, particularly when used in combination with chemotherapy. A challenging aspect of these immunotherapies is that they may show atypical therapy response patterns such as pseudoprogression and demonstrate a different imaging spectrum of adverse reactions, both of which are crucial for radiologists to understand. In 2017 the RECIST working group published a modified set of response criteria, iRECIST, for immunotherapy, based on RECIST 1.1 which was developed for cytotoxic therapies and adapted for targeted agents. CONCLUSION: This article provides guidance for response assessment of oncologic patients under immunotherapy based on iRECIST criteria.